A diploid assembly-based benchmark for variants in the major histocompatibility complex - Chen-Shan Chin (Nature Portfolio, 2020)
Accurate, phased assemblies are a key tool in understanding the human genome, particularly in highly polymorphic regions like the medically important MHC. Here the authors provide an assembly-based benchmark for this difficult-to-characterize region.